2022
DOI: 10.3389/fgene.2022.848627
|View full text |Cite
|
Sign up to set email alerts
|

Novel GBS-Based SNP Markers for Finger Millet and Their Use in Genetic Diversity Analyses

Abstract: Eleusine coracana (L.) Gaertn., commonly known as finger millet, is a multipurpose crop used for food and feed. Genomic tools are required for the characterization of crop gene pools and their genomics-led breeding. High-throughput sequencing-based characterization of finger millet germplasm representing diverse agro-ecologies was considered an effective method for determining its genetic diversity, thereby suggesting potential candidates for breeding. In this study, the genotyping-by-sequencing (GBS) method w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 58 publications
5
9
1
Order By: Relevance
“…As revealed through cluster and principal component analyses conducted based on randomly selected SNPs as well as SNPs within DEGs, there was high genetic variation among the finger millet genotypes, particularly among the Al-susceptible genotypes. The result is in line with previous SSR and SNP marker based studies on Finger millet (Brhane et al, 2021;Brhane et al, 2022). Despite the small number of samples, the fact that more genetic variation was detected in Alsusceptible genotypes than in Al-tolerant genotypes suggests that there is limited diversity in Al-tolerant finger millet.…”
Section: Ssr and Snp Markerssupporting
confidence: 90%
See 3 more Smart Citations
“…As revealed through cluster and principal component analyses conducted based on randomly selected SNPs as well as SNPs within DEGs, there was high genetic variation among the finger millet genotypes, particularly among the Al-susceptible genotypes. The result is in line with previous SSR and SNP marker based studies on Finger millet (Brhane et al, 2021;Brhane et al, 2022). Despite the small number of samples, the fact that more genetic variation was detected in Alsusceptible genotypes than in Al-tolerant genotypes suggests that there is limited diversity in Al-tolerant finger millet.…”
Section: Ssr and Snp Markerssupporting
confidence: 90%
“…These are accessions 215836 (from Gojjam), 215845 (from Bahir dar), 229722 (from Metekel), 212462 (from Hararge), 215804 (from Wellega), and 238323 (from Tigray). They were selected for sampling their representative genotypes based on the results of a preliminary hydroponic experiment, which was carried out as described in (Brhane et al, 2022). The results showed that the first three accessions (215836, 215845, and 229722) could be regarded as Al-tolerant whereas, the other three (212462, 215804, and 238323) are Al-susceptible.…”
Section: Plant Materials and Their Growth Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…While comparing the genetic differentiation, rice showed PhiPT value of 0.130 between the indica and japonica groups ( Luong et al., 2021 ), and the Ethiopian sorghum group showed 0.252 between B- and R-lines ( Mindaye et al., 2015 ). Finger millet revealed a moderate genetic differentiation (Fst = 0.352) among seven population sub-groups ( Brhane et al., 2022 ). Pearl millet demonstrated genetic differentiation at a PhiPT value of 0.130 for the chosen genotypes, similar to those studies.…”
Section: Discussionmentioning
confidence: 99%